From Catullus to Wikidata: Language Models, Metadata Schemas, and Ontologies in a Digital Edition in TEI - Nusch, Carlos Javier (2024)
This presentation describes the markup and natural language processing tasks undertaken in the Aetatis Amoris project, which explores love poetry and its textual patterns throughout literary history. ● In this early stage, the project focuses on the works of classical Latin poets such as Catullus, Tibullus, and Propertius. ● One approach involves using the TEI-XML standard to encode these texts.